2010
DOI: 10.4049/jimmunol.0903915
|View full text |Cite|
|
Sign up to set email alerts
|

HIV-Specific IL-21 Producing CD4+ T Cells Are Induced in Acute and Chronic Progressive HIV Infection and Are Associated with Relative Viral Control

Abstract: We examined the role of CD4+ T cell IL-21 production in viral control of HIV infection. HIV-infected individuals had greater circulating IL-21–producing CD4+ T cells in blood compared with uninfected volunteers. HIV-specific IL-21–producing CD4+ T cells were detected in blood during untreated acute and chronic HIV infection, and elevated frequencies of these cells correlated with relative viral control. These cells had an effector memory or end effector phenotype and expressed CXCR5. HIV-specific CD8+ T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 25 publications
(30 reference statements)
7
96
3
1
Order By: Relevance
“…In prior work we found that CXCL10 correlated with HIV load, while IL-17, CCL22, CXCL9, and fractalkine (CX3CL1) all showed inverse correlations with viral load (10). IL-21 has also been shown to inversely correlate with viral load (40). IL-10, IL-18, and soluble CD30 (sCD30) correlated positively with viral load in a cohort of subjects with low viral load (Ͻ1,000 RNA copies/ml) and noncontrollers (41).…”
Section: Discussionmentioning
confidence: 81%
“…In prior work we found that CXCL10 correlated with HIV load, while IL-17, CCL22, CXCL9, and fractalkine (CX3CL1) all showed inverse correlations with viral load (10). IL-21 has also been shown to inversely correlate with viral load (40). IL-10, IL-18, and soluble CD30 (sCD30) correlated positively with viral load in a cohort of subjects with low viral load (Ͻ1,000 RNA copies/ml) and noncontrollers (41).…”
Section: Discussionmentioning
confidence: 81%
“…Although we cannot fully exclude that the addition of exogenous recombinant IL-21 might skew the responses seen in vitro, these findings confirm via a separate approach the results of our multiplex bead based capture assay described above. Moreover, a recent publication ϩ T cells in long-term nonprogressors (Ͻ200 RNA copies/ml) (24). While the explanation for this discrepancy is not immediately apparent, it is interesting to note that Yue et al observed the highest level of HIV-specific IL-21-secreting CD4 ϩ T cells in individuals with "relative control" (defined as having viral loads between Ͼ200 and 20,000 RNA copies/ml).…”
Section: Fig 2 Il-21mentioning
confidence: 98%
“…Recent studies have highlighted the possible contribution of this cytokine to HIV control, with the findings that IL-21 in plasma correlates positively with CD4 counts (33) and that IL-21 secreted by HIV-specific CD4 ϩ T cells could induce a cytotoxic differentiation program with perforin induction in cognate CD8 ϩ T cells (11). Whether the frequencies of IL-21-producing specific CD4 ϩ T cells differ in HIV controllers and other patient groups remains debated, with one study showing an increase in the controller group (11) and two studies showing equivalent or lower levels (77,83). However, in the population of patients with detectable viremia, the persistence of IL-21-producing CD4 ϩ T cells is clearly associated with a beneficial outcome, as indicated by an inverse correlation with viral load (11,83) and a positive correlation with the frequency of IL-2 ϩ -specific CD8 ϩ T cells (77).…”
Section: Controller Cd4mentioning
confidence: 99%